Perancangan Sistem Informasi Pengambilan Nomor Antrian Berbasis Quick Response (Qr) Code pada UPT Samsat Medan Utara - Sianipar, Carmenita; Lubis, Andre Hasudungan (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2024)
This article or writing aims to retrieve queue numbers based on the Quick Response (QR) code. At first the retrieval system was done manually and using paper, this made paper use wasteful. In order to develop and facilitate the queue number retrieval system, this article was created based on a problem focused on quick response (QR) code based queue number retrieval. In order to approach this problem, theoretical references from related journals were used and they went directly to the UPT field. North Medan Samsat. The North Medan One-Stop Manungal Administration System Task Force Implementation Unit (UPT SAMSAT) is one of the SAMSATs in Medan that handles the arrangement of vehicle registration certificates (STNK) both for extending the period and for reversing names. Every day, many visitors come to take care of their STNK and result in visitors having to queue by taking a queue number using paper. Thus causing a lot of paper to be wasted because each queue number that has been taken by the next visitor will be discarded after the visitor's queue is over. The data were collected using actual data and analyzed qualitatively. This study concludes that taking queue numbers is based on a Quick Response (QR) code to make it easier for the public to speed up queues.